1995
DOI: 10.1681/asn.v5122037
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein restriction, blood pressure control, and the progression of polycystic kidney disease. Modification of Diet in Renal Disease Study Group.

Abstract: In the Modification of Diet in Renal Disease Study, a follow-up (mean, 2.2 yr) of 200 study participants with autosomal dominant polycystic kidney disease (ADPKD) was conducted to determine the effect of lowering protein intake and blood pressure on the rate of decline in GFR. The rate of decline was faster in participants with ADPKD than in persons with other diagnoses, reflecting, in part, faster disease progression in the ADPKD group. Baseline characteristics that predicted a faster rate of decline in GFR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(59 citation statements)
references
References 0 publications
3
54
0
2
Order By: Relevance
“…The observation that annualized eGFR slopes were similar in magnitude during REPRISE and OLE trials in subjects receiving tolvaptan in both trials suggested that reduced decline of eGFR among subjects in the REPRISE placebo data set in the OLE period (tolvaptan-treated) as compared with that in the REPRISE period (placebo-treated) was not a consequence of an unrelated slower pace of eGFR decline as suggested by data in the Modification of Diet in Renal Disease study. 8 Finally, changes from the REPRISE baseline during the OLE trial were larger in the REPRISE placebo subjects compared with the matched REPRISE tolvaptan subjects owing to the shorter duration of tolvaptan treatment in the former group, yet the change from REPRISE baseline slopes was comparable and parallel for the 1-year period regardless of previous treatment in REPRISE, indicating tolvaptan treatment effects were maintained in advanced CKD G4 (eGFR 15–29).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The observation that annualized eGFR slopes were similar in magnitude during REPRISE and OLE trials in subjects receiving tolvaptan in both trials suggested that reduced decline of eGFR among subjects in the REPRISE placebo data set in the OLE period (tolvaptan-treated) as compared with that in the REPRISE period (placebo-treated) was not a consequence of an unrelated slower pace of eGFR decline as suggested by data in the Modification of Diet in Renal Disease study. 8 Finally, changes from the REPRISE baseline during the OLE trial were larger in the REPRISE placebo subjects compared with the matched REPRISE tolvaptan subjects owing to the shorter duration of tolvaptan treatment in the former group, yet the change from REPRISE baseline slopes was comparable and parallel for the 1-year period regardless of previous treatment in REPRISE, indicating tolvaptan treatment effects were maintained in advanced CKD G4 (eGFR 15–29).…”
Section: Discussionmentioning
confidence: 86%
“…The control analysis was performed to reveal whether observed differences in eGFR decline in REPRISE compared with OLE for the REPRISE placebo subset were attributable to a tolvaptan treatment effect or alternatively to a plateau in eGFR decline in the OLE trial associated with late-stage kidney disease, as suggested by data from the Modification of Diet in Renal Disease. 8 …”
Section: Methodsmentioning
confidence: 99%
“…Several studies highlighted that animal protein intake can affect early kidney failure during ADPKD (Klahr et al, 1995;Ogborn and Sareen, 1995). A very interesting trial conducted from 2012 to 2014 (ClinicalTrials.gov NCT01810614) explored the correlation between diet and markers of ADPKD.…”
Section: Water Intakementioning
confidence: 99%
“…The KDIGO guidelines emphasize that the advantage of intensive BP lowering (SBP <120 mm Hg) is less certain in those with A3 albuminuria (>300 mg/g, or >30 mg/mmol), stage 5 CKD, or diabetics with CKD [12]. This statement is based on the results of several landmark clinical trials ( [13]; AASK: The African American Study of Kidney Disease and Hypertension [14]; REIN-2: Ramipril in non-diabetic renal failure Study-2 [15]; ACCORD: Action to Control Cardiovascular Risk in Diabetes Study [16]; BP: blood pressure; SBP: systolic blood pressure; MAP: mean arterial pressure; CKD: chronic kidney disease; GFR: Glomerular filtration rate; ESRD: end-stage renal disease.…”
Section: Blood Pressure Targetsmentioning
confidence: 99%